Modeling, Monitoring, and Validating Green Roof and Green Facade Solutions with Semantic City Models Using Low Cost Sensors and Open Software Infrastructures - Trang Thuy Vo; Alexandru Nichersu; Jochen Wendel (Urban Science, 2019)
The usage of greenery systems as nature-based solutions to assist in urban cooling in summer time as well as urban warming in wintertime is considered a scientific validated approach in urban planning. The objective of this research is the investigation and quantification of the role of green roofs and green facade solutions concerning thermal behavior in buildings energy savings by using standardized semantic city models that allow the quantification of such measures on district and city scales. The implemented model uses standardized geospatial data based on the CityGML format, a semantic city model standard, for analysis and data storage. For storage of the thermal properties of the buildings, the behavior of its occupants as well as the sensor measurements the Energy ADE of the CityGML standard was used. A green roof/façades model was implemented to simulate the heat transfer in a building based on the heat balance principle of foliage, soil, and structural layers. This model allows analyzing the thermal influence of plant and substrate layers on the heat gains from incoming solar radiation into buildings and the heat losses. This implementation was validated for cooling solutions using monitoring data from real-time experiments during summer measurements at three locations in Germany. Results from this experiment correspond well with the findings of other relevant studies. A sensitivity analysis was conducted to test the impacts of climate, substrate and plants on the greenery layer performance.